Transformasi Digitalisasi Pemasaran Di Niagaland Surabaya - nisaa, khoirun; Tsaqiffi, Najih; Syaffa, Firdaus; Aini, Saqofa Nabilah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study analyzes how digital transformation in Niagaland Surabaya implements marketing strategies. This type of research is a qualitative approach, while the data collection techniques are interviews and thematic analysis to identify the main patterns in the implementation of this strategy. The results of the study revealed that Niagaland actively uses social media, especially Facebook and WhatsApp, to reach customers in various locations, both near and far from the operational area. This can be supported by the fact that the company relies on fresh generation Z human resources, which produce creative and innovative content. The content produced, especially video content, will attract customers' attention because it is also relevant and interesting to them. Such an approach not only strengthens relationships with customers but also significantly expands Niagaland's market reach. The digital transformation implemented has been able to increase the effectiveness of the company's marketing. In addition, customers also get a better experience thanks to more personal interactions and interesting content. This study concludes that social media-based strategies and content creativity are the keys to Niagaland's success in utilizing digital transformation for its business growth..